Peptic ulcer and non-steroidal anti-inflammatory agents. Issue 8 (August 1986) - Duggan, J M; Dobson, A J; Johnson, H; Fahey, P
Abstract : Aspirin is generally regarded as a cause of gastric ulcer but the role of non-steroidal anti-inflammatory agents and paracetamol in the aetiology of peptic ulcer is unclear. To investigate this we conducted a case control study of 180 matched pairs of peptic ulcer patients and controls obtained from surgical and dermatology outpatient clinics. There were 95 gastric ulcer and 85 duodenal ulcer patients. A statistically and clinically association (relative risk = 5) was found between the regular use of non-steroidal anti-inflammatory agents and gastric ulcer. There was also evidence of positive associations between gastric ulcer and aspirin containing preparations with or without non-steroidal anti-inflammatory agents. By contrast, duodenal ulcer was unrelated to these drugs. Too few patients used paracetamol for any conclusion to be drawn on its role.